Perluasan Theory of Planned Behavior untuk Menjelaskan Green Purchase Intention Sepeda Motor Listrik di Jakarta - Suparman, Suparman; Supriyono, Supriyono (Indonesian Journal of Social Sciences and Humanities, 2026)
This study examines the determinants of Green Purchase Intention toward electric motorcycles in Jakarta by extending the Theory of Planned Behavior through the inclusion of Green Image as a mediating construct. A quantitative approach was employed using survey data collected from 150 prospective buyers who intend to purchase a motorcycle. Structural Equation Modeling with PLS was applied to assess the measurement and structural models. The results indicate that Green Attitude, Green Subjective Norm, and Green Perceived Behavioral Control significantly influence Green Image, which in turn exerts a substantial effect on Green Purchase Intention. Normative influence emerges as the most dominant predictor in shaping green image perceptions, highlighting the role of social evaluation in sustainable mobility decisions within an urban context. The model demonstrates moderate-to-strong explanatory power, confirming that image-based cognition strengthens the translation of psychological determinants into behavioral intention. These findings contribute to the theoretical refinement of TPB in green transportation research and provide practical implications for policymakers and industry actors seeking to accelerate electric motorcycle adoption in Jakarta.